The Relationship Of Family Support With Blood Sugar Levels In Clients With Diabetes Mellitus Type 2 In Poly Diseases In Blud Rsud Dr. Doris Sylvanus Palangka Raya - Natalansyah (International Journal of Science, Technology & Management, 2021)
International Diabetes Federation (IDF) estimates that there is an increase in the number of people with diabetes in Indonesia from 9.1 million in 2014 to 14.1 million in 2035. Type 2 diabetes is the most common type. Diabetes is a group of metabolic diseases characterized by hyperglycemia due to defects in insulin secretion, insulin action, or both. Diabetes mellitus can cause various physical or psychological changes or disorders for clients where they must depend on diabetes management therapy. The purpose of this study was to determine the relationship of stress levels with self-care to clients of type 2 diabetes mellitus at the Internal Medicine Poly Blud Rsud dr. Doris Sylvanus. This study used a cross-sectional study design, with a purposive sampling technique, the number of samples in this study were 35 respondents, collecting data using the Summary questionnaire The Summary of Diabetes Self-Care Activities (SDSCA and Diabetes Distress Scale (DSS) and analyzed using a test chi-square The results of this study indicate that of the 20 respondents who were severely stressed 18 respondents were not good at self-care and of the 15 respondents who experienced mild stress 10 respondents were able to perform self-care well. In the chi-square test results obtained p-value = 0.001, where the value of p <? (? = 0.05) can be concluded that there is a significant relationship between stress levels and self-care were the higher the level of stress, the lower the self-care behavior.